Comparison of cross‐platform flow cytometry minimal residual disease evaluation in multiple myeloma using a common antibody combination and analysis strategy. Issue 2 (17th November 2014) - Mathis, Stéphanie; Chapuis, Nicolas; Borgeot, Jessica; Maynadié, Marc; Fontenay, Michaela; Béné, Marie‐Christine; Guy, Julien; Bardet, Valérie
Abstract : Background: A seven‐color/eight‐antibody approach has recently been proposed for the minimal residual disease (MRD) determination in multiple myeloma (MM), which was developed on FACSCantoII instruments. This strategy should be also applicable on different multiparameter flow cytometers (MFC), but this needs to be demonstrated before moving MRD assessment to local flow cytometry core facilities, nearer to patients, thereby reducing the risk of cell losses induced by sample transportation and delays in cell processing. Methods: To evaluate the comparability of testing the same seven‐color/eight‐antibody single‐tube on any instruments, MRD was evaluated concomitantly on two distinct MFC in a cohort of 80 bone marrow MM samples (i.e., 73 patients including seven with two MRD evaluations) in two French centers, Paris‐Cochin and Dijon. Results: No significant difference in the MM residual plasma‐cells (MM‐PCs) quantification was observed. Calculated on the basis of the whole amount of leukocytes assessed, the mean MRD percentage was, respectively, 0.1661% and 0.1458% using FACSCantoII or Navios instruments, with a very high correlation between instruments ( r 2  = 0.9798) and a very minimal bias (−0.02). Moreover, there was no difference in MRD interpretation at 10 −4 threshold; whereas three MRD interpretation discordances were observed at 2.5 × 10 −5 threshold. Conclusion: This study demonstrates that this MRD‐detection strategy is transposable between harmonized ≥ seven‐color instruments. This shows that a homogeneous rapid MRD evaluation can be performed in most MFC platforms, in the near vicinity of clinical wards. However, the clinical validation of this approach needs to be strengthened, as well as its relevance compared to molecular approaches. © 2014 International Clinical Cytometry Society